2014
DOI: 10.1002/anie.201404208
|View full text |Cite
|
Sign up to set email alerts
|

A Reliable Aerosol‐Spray‐Assisted Approach to Produce and Optimize Amorphous Metal Oxide Catalysts for Electrochemical Water Splitting

Abstract: An aerosol-spray-assisted approach (ASAA) is proposed and confirmed as a precisely controllable and continuous method to fabricate amorphous mixed metal oxides for electrochemical water splitting. The proportion of metal elements can be accurately controlled to within (5±5) %. The products can be sustainably obtained, which is highly suitable for industrial applications. ASAA was used to show that Fe6Ni10O(x) is the best catalyst among the investigated Fe-Ni-O(x) series with an overpotential of as low as 0.286… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
153
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(158 citation statements)
references
References 32 publications
5
153
0
Order By: Relevance
“…Therefore, special attention has been paid to the development of synthetic methods that enable the composition control with a homogeneous distribution of elements. Such synthesis methods include electrodeposition, [29,93,[150][151][152][153][154][155] photochemical metal-organic deposition (PMOD), [156][157][158][159][160] aerosol-sprayassisted processes, [161,162] reactive magnetron co-sputtering, [163] solvothermal processes, [164] and thermal decomposition. [165] …”
Section: Amorphous Metal Oxidesmentioning
confidence: 99%
“…Therefore, special attention has been paid to the development of synthetic methods that enable the composition control with a homogeneous distribution of elements. Such synthesis methods include electrodeposition, [29,93,[150][151][152][153][154][155] photochemical metal-organic deposition (PMOD), [156][157][158][159][160] aerosol-sprayassisted processes, [161,162] reactive magnetron co-sputtering, [163] solvothermal processes, [164] and thermal decomposition. [165] …”
Section: Amorphous Metal Oxidesmentioning
confidence: 99%
“…Spherical structure is also favorable in terms of surface energy. Nanospheres are the most reported shape of amorphous materials in the last decade (see Table 1), and they can be composed of calcium carbonate (CaCO 3 ) [43][44][45][46][47], silicon (Si) [48][49][50][51][52], metals or their compounds [53][54][55][56][57][58][59][60][61]. CaCO 3 is abundant in the natural world, and a typical model system used to mimic the mineralization process of biominerals [43].…”
Section: Morphologies Of Amorphous Nanomaterials Spheresmentioning
confidence: 99%
“…The large number of under-coordinated atoms (good electron acceptors) and reactive sites at the surface means that amorphous materials also have the advantage over crystalline ones in their contact with the electrolyte and active substances (electron donors), which favors electrochemical processes. In regard to the merits discussed above, amorphous nanomaterials have already demonstrated their superior performance over bulk crystalline materials in various electrochemical applications, including lithium-and/or sodium-ion batteries [51,62,66,71,79,84,[96][97][98][99][100], super-or pseudo-capacitors [77,78,83], electrochemical water splitting [59] and sensors [72,81]. The amorphous CoSnO 3 @C nanoboxes reported by Wang et al [79] showed high initial discharge and charge capacities of around 1,410 and 480 mA h g −1 , respectively, as revealed in Fig.…”
Section: Applications Electrochemical Electrode Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a large overpotential is required to overcome the kinetic barrier induced by the high activation energy, and thus to form the reaction intermediates in the system, whatever for an anodic oxygen evolution reaction (OER) and a cathodic hydrogen evolution reaction (HER) [7]. For the practical water spitting, the effective catalysts are needed to decrease the overpotential of the reaction, thus making the process more energy-efficient [8][9][10]. In this regard, the state-of-the art precious metals (Pt, IrO 2 , RuO 2 ) for OER and HER have suffered from the high price and lack of reserves, thus limiting their applications for the overall water splitting [11][12][13].…”
Section: Introductionmentioning
confidence: 99%